MEDIASI PERSPEKTIF HUKUM ISLAM DAN HUKUM NASIONAL - Ilmiati Ilmiati (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
Mediation (peace) in Islamic law is referred to as islah, in etimology it is court verdict. Meanwhile, in terminology, it is a covenant with a view to end the case between two litigant parties. Stellingsrecht sees peace (islah) substantially same as what is implemented by Islamic law. Reconciliation in civil lawsuit is usually ascertained in Religious Court and District Court. Procedures for mediation in the courts are established with several phases started from the preparation to formulating agreement point - solely it succed, hence the importance of mediation as an alternative dispute resolution process, supporting regulations are required in order to make mediation institutions be able becoming one of the steps for settling disputes.